2011
DOI: 10.1371/journal.pone.0020277
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized LDL Receptor 1 (OLR1) as a Possible Link between Obesity, Dyslipidemia and Cancer

Abstract: Recent studies have linked expression of lectin-like ox-LDL receptor 1 (OLR1) to tumorigenesis. We analyzed microarray data from Olr1 knockout (KO) and wild type (WT) mice for genes involved in cellular transformation and evaluated effects of OLR1 over-expression in normal mammary epithelial cells (MCF10A) and breast cancer cells (HCC1143) in terms of gene expression, migration, adhesion and transendothelial migration. Twenty-six out of 238 genes were inhibited in tissues of OLR1 KO mice; the vast majority of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 29 publications
8
82
0
2
Order By: Relevance
“…It also follows from our microarray analysis [72,73] that stimulation by interferon of some genes reported in the [145] study may be LOX-1 mediated. In LOX-1 KO transcriptome, the classical interferon target genes such as ISG20, and transcription factors IRF2 and IRF7 were significantly inhibited, which suggests an upstream position for LOX-1 in this signaling sequence.…”
Section: Tumor Antigensmentioning
confidence: 66%
See 1 more Smart Citation
“…It also follows from our microarray analysis [72,73] that stimulation by interferon of some genes reported in the [145] study may be LOX-1 mediated. In LOX-1 KO transcriptome, the classical interferon target genes such as ISG20, and transcription factors IRF2 and IRF7 were significantly inhibited, which suggests an upstream position for LOX-1 in this signaling sequence.…”
Section: Tumor Antigensmentioning
confidence: 66%
“…Moreover, treatment of MCF-10A cells with a low concentration of ox-LDL induced cellular transformation and colony formation in NF-κB-dependent manner. Taken together, these observations suggest that LOX-1 is an important molecule mechanistically linking metabolic syndrome to cancer and acting through regulation of inflammatory and hypoxia responses during transformation Our analysis of LOX-1 knockout transcriptome [72,73] revealed that about 10% of genes upregulated during transformation were inhibited by more than 20% in tissues of LOX-1 deficient mice with most of them containing NF-κB binding site in their proximal promoter regions. Altogether, LOX-1 abrogation inhibited a quarter of all NF-κB target genes with the prevailing enrichment themes of apoptosis, proliferation, wound healing and defense.…”
Section: Scavenger Receptorsmentioning
confidence: 73%
“…ROS and receptor-dependent effects of cytokines and modified low-density lipoprotein (LDLs) are associated with an impaired energy function and apoptotic signaling of mitochondria, and cause ER stress through either Ca-dependent or -independent signaling in different types of cells [21,22]. At the same time, ROS and the binding of oxidized LDL (Ox-LDL) to scavenger receptors of endothelial cells activates the proinflammatory transcription factor as NF-ĸβ [23,24], inhibits the transcriptional activity of PPAR-γ [25] and causes the accelerated senescence of endothelial progenitor cells [22]. These events altogether may sustain vascular microinflammation, arterial calcifications and atherosclerotic plaque formation by means of different underlying events such as (1) a defective capability of the arterial wall to prevent lipid deposition and foam cell formation, (2) a lowered capability to regulate the remodeling of the extracellular matrix and calcium deposition, (3) impaired mechanisms of prevention of leukocyte and platelet activation, and (4) poor repair of endothelial cell damage.…”
Section: Bioincompatibility Microinflammation and Oxidative Stress: mentioning
confidence: 99%
“…They also elucidated the upregulation of LOX-1 in relation to the relative cholesterol deficiency in hypertrophic adipocytes which need to induce the expression of cholesterol receptors such as LOX-1 to create a cellular environment that increases the total cholesterol content, promotes free fatty acids (FFA) uptake and enhances lipid storage [87]. Recently, microarray findings in mice tissues showed that LOX-1 deletion results in inhibition of key enzymes for lipogenesis, including ATP citrate lyase (Acly), acetyl-Coenzyme A carboxylase alpha (Acaca), fatty acid synthase (Fasn), stearoyl-CoA Desaturase 1 (Scd1) and ELOVL family member 6 (Elovl6) [91]. It is of interest that none of the LOX-1-sensitive lipid metabolism related genes carries NF-κB binding sites in their promoters.…”
Section: Lox-1 and Obesitymentioning
confidence: 99%